2005
DOI: 10.2527/2005.83112637x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mannan oligosaccharide and an antimicrobial product in nursery diets on performance of pigs reared on three different farms1

Abstract: The objective of this experiment was to compare the effects of dietary mannan oligosaccharide (MOS) and a feed-grade antimicrobial (AM) on growth performance of nursery pigs reared on three different farms (A and B were large-scale commercial farms, and C was located at Michigan State University). On all farms, production was continuous flow by building, but all-in/all-out by room. Within each nursery facility, all pigs on the experiment were in one room. Pigs (Farm A, n = 771, weaning age = 18.4 d; Farm B, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 5 publications
2
29
0
6
Order By: Relevance
“…Such potential enhancement of daily weight gain by FWGE might be considerable in terms of production efficiency due to reduction of the time between weaning and finishing. This improvement is comparable to those obtained with growth promoter antibiotics in pigs of similar weight (e.g., Rosenboom et al, 2005). Antibiotic replacers/alternatives such as copper and zinc, organic acids, essential oils, probiotics, prebiotics (predominantly with fructose-oligosaccharides, FOS) were reported to improve the growth rate of pigs at different extent.…”
Section: Immunological Examinationssupporting
confidence: 66%
“…Such potential enhancement of daily weight gain by FWGE might be considerable in terms of production efficiency due to reduction of the time between weaning and finishing. This improvement is comparable to those obtained with growth promoter antibiotics in pigs of similar weight (e.g., Rosenboom et al, 2005). Antibiotic replacers/alternatives such as copper and zinc, organic acids, essential oils, probiotics, prebiotics (predominantly with fructose-oligosaccharides, FOS) were reported to improve the growth rate of pigs at different extent.…”
Section: Immunological Examinationssupporting
confidence: 66%
“…Through this mode of action, GAC has been shown to improve animal health and performance. Published data have shown consistent improvements in piglet, sow, broiler and turkey performance (Miguel et al, 2002;Hooge et al, 2003;Sims et al, 2004;Hooge, 2004a and2004b;Rozeboom et al, 2005) where GAC has been fed over a continuous period of time. In many cases, this work has been focused on the practical replacement of antibiotic growth promoters in animal feeds, and maintenance of the performance of the groups of animals (Hooge, 2004a and2004b).…”
Section: Introductionmentioning
confidence: 82%
“…However, only a few in vivo studies indicated that selected glycans decrease illness incidence in piglets. For example, dietary mannan oligosaccharides promoted the growth of nursery piglets in three farms (20), and chitooligosaccharide increased the growth of weaning piglets and decreased the incidence of diarrhea (21). The limited number of animal studies, however, hampers practical application of dietary glycans to prevent pathogen adhesion.…”
mentioning
confidence: 99%